ChemInform Abstract: An Overview on Phase Equilibria and Thermodynamic Modeling in Multicomponent Al Alloys: Focusing on the Al‐Cu‐Fe‐Mg‐Mn‐Ni‐Si‐Zn System. Issue 4 (31st January 2013) - Du, Yong; Liu, Shuhong; Zhang, Lijun; Xu, Honghui; Zhao, Dongdong; Wang, Aijun; Zhou, Liangcai
Abstract Review: 143 refs.